(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
Construction of gravel basket weir in waterways causes water accumulation in front of this porous structure less than solid weir. In the present study the upstream flow depth, water surface profile and discharge coefficient are investigated through laboratory experiments. Four different weir lengths (15, 20, 25 and 30 cm) and four different degrees of gravel coarseness (1.13, 1.58, 2.19 and 2.27) are studied. Accordingly, sixteen models are tested under different free flow conditions. Analysis of the results show that in "through flow" regime the increase in weir length raises the generated upstream depth for all coarseness degrees by 30% while coarseness lowers the depth by 28%. In "transition flow", however, doubling the length increases the flow depth by 7%, but increasing coarseness from 1.13 to 2.72 cm mean diameter causes 7% reduction in flow depth. The "overflow" regime begins to appear when the depth to length ratio equals 0.75 for long weir, and about 1.54 for shortest weir. A comparison between gravel basket weir and corresponding solid weir indicates that average depth reduction is 7.5% for coarseness of 1.13 cm and 9% for coarseness of 2.72 cm. Mathematical models for water depth prediction for the three flow regimes are presented. For "overflow" an empirical formula is proposed to estimate the coefficient of discharge with acceptable accuracy.